Gender Equality Policy in Sweden: 1970s–2010s - Nyberg, Anita (Nordic Journal of Working Life Studies, 2012)
The aim of this article is to give an overview of gender equality policy in Sweden from the 1970s until today. A number of political measures and whether these measures individually, as well as combined, have promoted gender equality and the dual-earner/dual-carer model are described and analyzed. The conclusion is that the right to part-time work, publicly financed child care, parental leave, and tax deductions for domestic services make it easier for mothers to reconcile work and family, but do not challenge the distribution of family responsibilities between women and men. However, the individual right for fathers to 2 months of parental leave does challenge the gender order, to a certain extent, and fathers today participate more in care and domestic work than earlier. The dual-earner/dual-carer family is closer at hand when women have a higher education and earnings and thereby greater bargaining power. Employed work is more conditional among women with a lower education level, i.e., they may be employed but under the constraint that they are still responsible for care and domestic work in the family. Another constraint in this group where many work part-time is the lack of available full-time positions in the labor market.